2018
DOI: 10.1042/bsr20171721
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin A increases allograft tolerance in an experimental transplantation model: a preliminary study

Abstract: BackgroundIdentifying novel and safe immunosuppressants is of crucial importance. Recently, there have been several studies revealing that botulinum toxin A significantly alleviates ischemia-reperfusion injuries.Emerging evidence shows that ischemia-reperfusion injuries contribute to innate immune activation, promoting rejection and inhibiting tolerance. Therefore, we hypothesized that a pretreatment with botulinum toxin A might decrease allograft rejection in a rat transplantation model. MethodsTwenty-four Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Park and Park [30] demonstrated that BTXA treatment might increase the expression of VEGF and yield protection against ischemiareperfusion injury depending on increasing angiogenesis. Other studies also concluded that the group with BTXA treatment had higher VEGF expression in a rat transplantation model or transverse rectus abdominis myocutaneous flap in a rat model [31,32]. The concentration of BTXA used in these studies was 10 IU/mL, but Gugerell et al [33] found that high BTXA concentration of 20 IU/mL might reduce VEGF expression and inhibit angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Park and Park [30] demonstrated that BTXA treatment might increase the expression of VEGF and yield protection against ischemiareperfusion injury depending on increasing angiogenesis. Other studies also concluded that the group with BTXA treatment had higher VEGF expression in a rat transplantation model or transverse rectus abdominis myocutaneous flap in a rat model [31,32]. The concentration of BTXA used in these studies was 10 IU/mL, but Gugerell et al [33] found that high BTXA concentration of 20 IU/mL might reduce VEGF expression and inhibit angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies on SP-aided transplants is still ambiguous. For example, the use of botulinum toxin A during skin transplantation in murine models enhances the expression of VEGF and prolonged the survival of skin grafts (148). By contrast, Kucukkaya et al (149) demonstrated that the same toxin reduces wound-graft contraction.…”
Section: Potential Of Sps As Novel Alternatives For Wound Healing Carementioning
confidence: 99%
“…Renal tubular epithelial cells are the cells most severely damaged in response to IRI ( 8 ). IRI results in the loss of tubular epithelial cell function, leading to acute renal injury, delayed graft function, and acute and chronic organ rejection ( 9 , 10 ). Mitochondrial autophagy and ferroptosis also occur in renal tubules in response to IRI ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%